Urban Youth in Transformation: Considerations for a Sociology of Trap Subculture - Conti, Uliano (Italian Sociological Review, 2020)
The article considers the theme of urban subcultures and focuses on the evolution of hip hop subculture. Hip hop subculture is made up of elements such as writing, break-dance, djing and rap. Rap as a musical genre changes over time, with the affirmation, for example, of Gangsta-rap. Recently, the Trap music genre has also emerged. The main features of Trap are identifiable in the rhetorical topoi of violence, individualism, references to drugs and urban suburbs. The paper analyses these characteristics and relates them to traditional rap, highlighting what the Trap genre communicates about urban suburbs and marginal young people.